Shallow versus deep integration between mediterranean countries and the EU and within the mediterranean region - Ahmed Farouk Ghoneim; Javier Lopez Gonzalez; Maximiliano Mendez Parra; Nicolas Peridy (Center for Social and Economic Research (CASE), 2011)
The paper aims at assessing the specific impact of shallow versus deep integration between Mediterranean (MED) countries1 and their partners in the European Union (EU) as well as between the MED countries themselves. It relies on dataset developed for this project concerning tariffs (as a proxy for shallow integration) and Non Tariff Measures (NTMs)2 (as a proxy for deep integration). Additional data are also included in order to take into account other trade costs, especially transport costs and logistics costs. In this regard, an original dataset of maritime freight cost (Maersk, 2007) is introduced as well as the trade logistics performance (TLP) index produced by the World Bank. Such datasets are useful for providing additional insight into deep integration. The paper starts by calculating the magnitude of NTMs in terms of ad valorem tariff equivalent (AVEs). The estimation of NTMs through ad valorem equivalents (AVEs) shows that Algeria and Jordan have the highest value of AVEs, whereas Tunisia, Morocco, and Egypt have the lowest value. A gravity model is then estimated with special emphasis on trade costs which are the crucial point in our research study. Given the limitation of data on NTMs, the gravity model is estimated for only one year (2001), and for each MED country. Trade costs are represented by tariffs, AVEs of NTMs, and transport and logistics costs. The idea is to test which of the three elements of trade costs are the most impeding to bilateral trade between MED countries and EU countries as well as amongst MED countries. The model shows that tariffs, NTMs, and trade and logistics costs have a significant impact on trade, but is highly vivid in countries suffering from high tariff rates, prevalence of NTMs, and trade costs. A number of simulations are carried out trying to differentiate between the impact of partial liberalization and full liberalization on trade creation. The results obtained show that full liberalization has a significant effect whether it is only related to shallow integration (tariff removal) or deep integration (NTMs and trade and logistics). The effect is higher if trade costs and logistics are improved. The results are far less if only partial liberalization takes place and in several countries is insignificant implying that marginal reductions in NTMs or tariffs cannot always help to create trade. Finally the study shows that there is a huge potential for enhancing trade amongst MED countries if trade costs are lowered, logistics is improved, and NTMs are abolished.
Keywords: F15; F17; 330; Regional Trade Agreements; Regional Integration; Non-Tariff-Measures; Deep versus shallow integration; South Mediterranean countries; European Union Trade Agreements; Regionale Wirtschaftsintegration; Regionale Wirtschaftsintegration; Zoll; Nichttarifäre Handelshemmnisse; Gravitationsmodell; Mittelmeerraum; EU-Staaten